2012
DOI: 10.1016/j.pss.2011.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Titan's lakes chemical composition: Sources of uncertainties and variability

Abstract: Between 2004 and 2007 the instruments of the CASSINI spacecraft, orbiting within the Saturn system, discovered dark patches in the polar regions of Titan. These features are interpreted as hydrocarbon lakes and seas with ethane and methane identified as the main compounds. In this context, we have developed a lake-atmosphere equilibrium model allowing the determination of the chemical composition of these liquid areas present on Titan. The model is based on uncertain thermodynamic data and precipitation rates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…While much theoretical work has been reported concerning the solubility values of organic materials in Titan fluids (Cordier et al, 2013(Cordier et al, , 2012(Cordier et al, , 2009Shock, 2013a, 2013b;Dubouloz et al, 1989;Raulin, 1987), little experimental work has been done. The bulk of the experimental work has examined the solubility of hydrocarbons in nitrogen-equilibrated and pure methane solutions (Szczepaniec-Cię ciak et al, 1978;Preston et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While much theoretical work has been reported concerning the solubility values of organic materials in Titan fluids (Cordier et al, 2013(Cordier et al, , 2012(Cordier et al, , 2009Shock, 2013a, 2013b;Dubouloz et al, 1989;Raulin, 1987), little experimental work has been done. The bulk of the experimental work has examined the solubility of hydrocarbons in nitrogen-equilibrated and pure methane solutions (Szczepaniec-Cię ciak et al, 1978;Preston et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…These change the fluid ratio and may modify the solubilities. Previous calculations by Cordier et al (2012) Table 3 in their text) suggested that a 10% decrease in atmospheric pressure over a Titan lake of mixed hydrocarbons and nitrogen would have a <2% increase in benzene solubility. This is driven primarily by the effect of pressure changing the overall composition to a more ethane-rich fluid in equilibrium with the atmosphere as the volatiles, methane, and nitrogen leave the solution.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Nearly all the surface liquids discovered to date are contained in the polar lakes, which are largely confined to north of latitude 55 • and range in size from 10 to 10 5 km 2 (Hayes et al 2008). Titan's lakes are a mix of methane, ethane, and dissolved nitrogen and heavier hydrocarbons, although the exact ratio of ingredients is uncertain (Cordier et al 2012). The rest of the surface is devoid of lakes, except the south polar region, which is covered in considerably fewer lakes than the north polar region but notably has Ontario Lacus.…”
Section: On the Surfacementioning
confidence: 99%